2003
DOI: 10.1902/jop.2003.74.9.1381
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Giant Cell Granuloma Associated with Dental Implants

Abstract: Peripheral giant cell granuloma can develop in association with dental implants. Clinically, the lesions are similar to the classical PGCG. In the present study, the precise incidence could not be concluded because of the small number of selected cases. Due to the aggressive nature of the lesion and the high recurrence rate, implants can fail unless the lesion is detected early and proper surgical removal is performed. Tissue removed from the peri-implant area should always be submitted for histologic examinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
68
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 7 publications
9
68
0
1
Order By: Relevance
“…The uniqueness of this clinical case lies in a possible correlation between classical peri-implantitis and the concomitant occurrence of a giant-cell granuloma. Similar cases were found with mandibular implants [7].…”
Section: Discussionsupporting
confidence: 83%
“…The uniqueness of this clinical case lies in a possible correlation between classical peri-implantitis and the concomitant occurrence of a giant-cell granuloma. Similar cases were found with mandibular implants [7].…”
Section: Discussionsupporting
confidence: 83%
“…9 A few articles on peripheral giant cell granuloma associated with dental implants have also been published. [10][11][12][13] In our case we found a PG in relation to a dental implant. A literature survey did not find any articles on PG associated with dental implants.…”
Section: Discussionmentioning
confidence: 83%
“…Only 6 cases have been reported in the international literature 3,5,10,20 . To the best of the authors' knowledge, this is the first case of pyogenic granuloma reported in association with a dental implant.…”
Section: Discussionmentioning
confidence: 99%